THE ASSOCIATION BETWEEN SCREEN TIME AND PSYCHOLOGICAL DISTRESS AMONG INDONESIAN FEMALE ADOLESCENTS: A CROSS-SECTIONAL STUDY - Feriyanti, Alma; Agustini , Rina Tri; Permana , Lies; Rohmah, Nur; Nurrachmawati , Annisa; Rahayu, Agustin Putri; Fikri, Mohammad (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2025)
Background: Excessive smartphone use has a negative impact on health, especially in the adolescent age group. Adolescent females who screen time for two hours or more a day after school have the potential to experience psychological distress. Purpose: To analyze the relationship between screen time behavior and psychological distress in high school adolescent females. Methods: This quantitative study using a cross-sectional design. The research locations were carried out in three schools, namely SMA (Senior High School) 9 Balikpapan, SMA 2 Samboja and SMA 3 Penajam Paser Utara. The population was 1,112 adolescent females and the sample was 272 adolescent females. The sampling technique used was proportional random sampling. The analysis test used the chi-square test. Variable measurements of screen time and psychological distress are used in the Questionnaire for Screen Time of Adolescents and the Kessler Psychological Distress Scale. Results: The p-value < 0.05 means that there is a relationship between screen time and psychological distress in high school adolescent females. Conclusion: Excessive screen time has an impact on the psychological distress of high school females. There is a need to increase mental health literacy and support for parents and schools in restricting the use of smartphones at home and at school. Abstrak Latar Belakang: Penggunaan smartphone yang berlebihan berdampak negatif pada kesehatan terkhususnya pada kelompok usia remaja. Remaja putri yang melakukan screen time selama dua jam atau lebih perhari setelah pulang sekolah berpotensi mengalami tekanan psikologis. Tujuan: Menganalisis hubungan antara perilaku screen time dan tekanan psikologis pada remaja putri sekolah menengah atas. Metode: Merupakan penelitian kuantitatif dengan menggunakan desain cross-sectional. Lokasi penelitian dilaksanakan pada tiga sekolah yaitu SMA 9 Balikpapan, SMA 2 Samboja dan SMA 3 Penajam Paser Utara. Populasi pada penelitian ini sebesar 1.112 remaja putri dan sampel penelitian yaitu sebanyak 272 remaja putri. Teknik sampling yang digunakan yaitu proportional random sampling. Uji analisis menggunakan uji chi-square. Pengukuran variabel screen time dan tekanan psikologis menggunakan Questionnaire for Screen Time of Adolescents dan Kessler Psychological Distress Scale. Hasil: Nilai p-value < 0,05 yang artinya ada hubungan antara screen time dengan tekanan psikologis pada remaja putri sekolah menengah atas. Kesimpulan: Screen time berlebihan memiliki dampak pada tekanan psikologis pada remaja putri sekolah menengah atas. Perlu adanya peningkatan literasi kesehatan mental serta dukungan orang tua dan sekolah dalam memberikan pembatasan penggunaan smartphone di rumah maupun di sekolah.